THE INFLUENCE OF LEADERSHIP STYLE, AND MOTIVATION WORK ENVIRONMENT ON EMPLOYEE WORK ACHIEVEMENT ENGKU HAJI DAUD HOSPITAL PROVINCE OF RIAU ISLANDS - Hariansyah, Herry; Indrayani, Indrayani; Satriawan, Bambang; Ngaliman, Ngaliman; Wibisono, Chablullah (CV. Radja Publika, 2022)
This research was conducted to determine the effect of leadership style, motivation, and work environment on employee work performance at Engku Haji Daud Hospital, Riau Islands Province. The sample in this study were 20 employees. The data collection technique used in this study was a questionnaire. The results showed that: 1) There is a positive effect of style Leadership on Employee Work Performance, There is a positive influence and motivation on Employee Work Performance and there is a positive influence on the Work Environment on Employee Work Performance.